The Influence of Credit Interest Rates and Third Party Funds on Credit Distribution at PT B PR BKK Banjarharjo, Brebes Regency - Muhammad Fahmi Hidayat; Nasiruddin Nasiruddin; Dumadi Dumadi; Anisa Sains Kharisma; Roni Roni (International Journal of Economics, Management and Accounting, 2026)
This study examines the influence of credit interest rates and third-party funds on the credit distribution of PT BPR BKK Banjarharjo, Brebes Regency, using a quantitative approach based on secondary data from monthly financial reports between 2020 and 2024, amounting to 60 observations. The results show that, partially, credit interest rates exert a negative and significant effect on credit distribution, while third-party funds demonstrate a positive and significant impact. Simultaneous testing further confirms that both variables collectively have a significant influence on credit distribution. These findings emphasize the importance of banking institutions in carrying out their intermediation function effectively, where the ability to maintain competitive credit interest rates and strengthen public fund mobilization becomes a strategic necessity to improve credit growth and financial stability. Moreover, the study highlights the role of micro-banking as a foundation for regional economic development, particularly in rural areas where local banks serve as drivers of community empowerment and sustainable economic activity. By reinforcing prudent management of interest rates and optimizing fund collection, banks can ensure not only improved financial performance but also the expansion of credit access for micro, small, and medium enterprises. The outcomes of this research are expected to provide practical contributions to policymakers in the banking sector, enrich scientific literature in financial management, and serve as a relevant reference for subsequent studies focusing on credit distribution, financial intermediation, and the development of microfinance institutions.